2017
DOI: 10.1186/s40249-016-0211-0
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of Schistosoma Antibodies and exploration of associated factors among local residents around Inlay Lake, Southern Shan State, Myanmar

Abstract: BackgroundSchistosomiasis is a chronic parasitic disease caused by blood flukes (trematode worms) of the genus Schistosoma. Its transmission has been reported in 78 countries affecting at least 258 million people world-wide. It was documented that S. japonicum species was prevalent in Shan State, Myanmar, but the serological study was not conducted yet. General objective of the present study was to detect schistosoma antibodies and explore associated factors among local residents living around Inlay Lake, Nyau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…In regards to control, little has been done to target definitive hosts of S. japonicum , with the exception of P.R. China, which has practiced both chemotherapy of bovines and removal of the animals, facilitated by mechanization of agriculture (i.e., replacing water buffalo with tractors) [16,29,89,100,101]. Without targeting intermediate host snails, re-infection of humans after treatment can occur almost instantaneously.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In regards to control, little has been done to target definitive hosts of S. japonicum , with the exception of P.R. China, which has practiced both chemotherapy of bovines and removal of the animals, facilitated by mechanization of agriculture (i.e., replacing water buffalo with tractors) [16,29,89,100,101]. Without targeting intermediate host snails, re-infection of humans after treatment can occur almost instantaneously.…”
Section: Epidemiologymentioning
confidence: 99%
“…Limited information is available regarding risk factors and snail intermediate hosts in Myanmar [16]. The current areas where schistosomiasis occurs are around Lake Inlay in Shan State, although a recent outbreak has occurred in Rakhine State on the Coast of the Bay of Bengal [143].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…7 This development made government to focus their attention for building up vector control programme based upon selective springing, personal protection method, including insecticide treated nets (ITNS) that can be carried out by the communities. 8 The recent world malaria report which indicated that Nigeria accounts for a quarter of all malaria cases in 45 malaria-endemic countries in Africa, clearly shows the challenge of malaria in Nigeria. While there are reports of up to 50% reduction in malaria episode and deaths in some African countries between 2000 and 2006, reports from Nigeria has not shown any significant reduction, especially with regards to malaria in pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…While there are reports of up to 50% reduction in malaria episode and deaths in some African countries between 2000 and 2006, reports from Nigeria has not shown any significant reduction, especially with regards to malaria in pregnancy. 2,4,8 The reasons adduced for change in malaria prevalence in other countries were good surveillance and high intervention coverage. 4,9 The WHO's RBM initiative launched in 1998 was targeted at the prevention and management of malaria during pregnancy using ITNS, among other measures 10 .…”
Section: Introductionmentioning
confidence: 99%